The relationship between the board of director characteristics and financial reporting quality - WU, LINGKE (2017)
We examine the relationship between the board of director characteristics and financial reporting quality. By using the logit regression model for a five-year analysis of 100 companies, the establishment of the audit committee can improve the quality of financial reporting. The increase in the number of female directors will increase financial fraud. The increase in the proportion of directors may stimulate financial fraud.